2014
DOI: 10.1177/1403494814556647
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and school attendance in adolescence: Results from a large population-based study

Abstract: The demonstrated relationship between sleep problems and school absence suggests that careful assessment of sleep is warranted when adolescents present with extensive school absence future studies on how the sleep-school absence relationship in adolescence may impact later work affiliation in adulthood are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 30 publications
9
44
0
1
Order By: Relevance
“…School attendance is also important for academic success. One report found that short sleep duration was strongly associated with odds of school absences . Several studies included in this review found that earlier start times were also related to more frequent tardiness and more absences .…”
Section: Methodsmentioning
confidence: 75%
“…School attendance is also important for academic success. One report found that short sleep duration was strongly associated with odds of school absences . Several studies included in this review found that earlier start times were also related to more frequent tardiness and more absences .…”
Section: Methodsmentioning
confidence: 75%
“…[14] Finally, the explained variance of the model is relatively small, and indicates that this is just one of many factors that are related to school absence. Other factors known to be associated with school absence such as for instance sleep problems [23] and alcohol and drug use [24] may also be of importance and were not addressed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…DSP may also impact academic performance indirectly through tardiness or school non-attendance, and previous reports from the youth@hordaland study have indeed recently showed increased school absence in adolescents presenting with DSP or other sleep problems [8,11]. Finally, there may be other factors, such as socioeconomic status, lifestyle behaviors (smoking, alcohol use and overweight), mental health problems and daytime sleepiness, known to be related to both sleep timing disturbance [12] and school performance [13], that might account for some of the association.…”
Section: Introductionmentioning
confidence: 97%